PEMBERDAYAAN PKK PERUM SAPPHIRE REGENCY PURWOKERTO MELALUI PELATIHAN PUBLIC SPEAKING OLEH FAKULTAS ILMU SOSIAL DAN ILMU POLITIK, UNIVERSITAS JENDERAL SOEDIRMAN TAHUN 2023 (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Through the era of openness and technological advances, the ability to communicate effectively, especially in public speaking, has become a very important skill for every individual. PKK (Family Empowerment and Welfare) Perum Sapphire Purwokerto Regency, as a community-level women's organization, has great potential to bring about change in its community. However, there are challenges to improving the ability of its members to speak in public. Seeing this, General Soedirman University Social Sciences and Political Sciences initiated a community engagement program that aims to provide public speaking training to members of the PKK Perum Faculty of Sapphire Regency. The training program is designed to improve self-confidence, delivery techniques, and the ability to answer audience questions. By using a series of training methods that involve interaction, participants are given the opportunity to train themselves and receive direct feedback from experts. The results of this program show a significant increase in the public speaking abilities of PKK members, so it is hoped that it can have a positive impact on PKK activities and programs at Perum Sapphire, Purwokerto Regency. The purpose of this article is to document the process, methodology, and results of the training that has been carried out, as well as provide recommendations for similar initiatives that may be carried out in the future.